Verbs' unaccusativity in existential constructions - Zhangyan Miao (Journal of Child Language Acquisition and Development)
The Unaccusative Hypothesis(UH) advocates the dominance of syntactic structure in assigning semantic values to sentence arguments. The same thematic roles should only be assigned by the same syntactic configuration. In recent studies, however, the unaccusative hypothesis was highly contentious and controversial and faced several problems. Certain verbs classified as unaccusative or unergative based on semantic or syntactic criteria do not conform to expectations due to the prevalence of unaccusative mismatches. Based on the previous cross-linguistic studies, this paper is motivated to focus on the nature of unaccusativity by a thorough syntactic and semantic dissection for verbs in existential constructions. It is argued that unaccusativity is primarily determined by syntactic positions rather than semantic features by providing a distributional pattern of verbs entering into existential constructions.